Inter-layer multi-material powder bed fusion additive manufacturing of a chainmail-like 3D interlocking bonding structure - Zixiong Lin; Hongchun Wu; Zheng Zhang; Jianghong Huang; Wenxiong Lin; Hailong Shao; Jinni Shen; Yuchao Wang; Fengyi Zhang; Mingsong Zheng; Shoufeng Yang (Virtual and Physical Prototyping)
Multi-material additive manufacturing (AM) has enabled on-demand material integration by combining distinct properties and functionalities to achieve performance unattainable with single materials, while significantly enhancing design freedom. However, high-precision multi-material AM still presents substantial challenges. Herein, a 3D interlocked chainmail-like Ti64/CP-Ti bioinspired composite with metallurgical bonding interfaces was fabricated via inter-layer multi-material laser powder bed fusion (LPBF) AM. The composite exhibits numerous 100-μm-scale structural features, reflecting cross-scale complexity, enhanced precision, and advanced manufacturing capabilities. Tensile tests showed that under 0° loading conditions, the composite achieved strength of 875 ± 21 MPa (80.5% higher than CP-Ti) and ductility of 7.4 ± 1.6% elongation (28.5% higher than Ti64). Finite element analysis incorporating a modified Johnson-Cook (JC) model reveals that off-axis loading (22.5°/45°) leads to performance degradation due to (1) diminished load-transfer efficiency of the Ti64 skeleton and (2) severe interfacial shear localisation, where shear stresses exceed 240 MPa at 20s(45° loading) and propagate extensively with strain. Cross-interface microhardness mapping indicates powder-spreading-direction-dependent hardness variations. This work establishes a paradigm for bioinspired anisotropic engineering composites (numerous 100-μm-scale structural features), where Ti64 governs strength via architectural control while CP-Ti enhances damage tolerance through strain delocalisation, offering direct implications for load-adaptive aerospace structures.